Building a Sustainable Future: Challenges, Opportunities, and Innovative Strategies for Destination Branding in Tourism - Eliyas Ebrahim Aman; Árpád Ferenc Papp-Váry; Deborah Kangai; Sebastian Ongango Odunga (Administrative Sciences)
The current sustainability concerns affect visitors’ behavior and competitiveness of destinations. For these reasons, the destinations need sustainable and innovative branding to address sustainability concerns, stand out in a competitive market, meet changing visitor preferences, and ensure long-term competitiveness in a dynamic global environment. In this regard, identifying and understanding challenges, opportunities, and innovative strategies are critically important. An integrative literature review method was employed using the Scopus database. The study identified major challenges, such as growing environmental concerns, the dynamic advancement of new technologies and artificial intelligence, health and safety concerns, diversity and inclusion, economic and geopolitical uncertainties, local community engagement, and competitive markets. Conversely, responsible tourism, the digital landscape, wellness and health, cultural festivals and events, accessibility and inclusivity, creative industries, and authenticity have been identified as future tourism branding opportunities. Based on the literature insights, the paper provides readers with essential information and advances the field of tourism and hospitality as it identifies challenges, opportunities, and innovative branding strategies in the industry. Furthermore, this work contributes to existing literature and proposes future research agendas.